Personalized dietary advices provided by a dietitian increase calcium intake in outpatients with multiple sclerosis—Results from a randomized, controlled, single-blind trial - Fiorella, Sandrine; Agherbi, Hanane; El Houjeiry, Emilia; Castelnovo, Giovanni; Renard, Dimitri; Privat, Pauline; Santamaria, Elodie; Vallayer, Virginie; Alonso, Sandrine; Chevallier, Thierry; Bancal, Candice; Laurent-Chabalier, Sabine; et al. (Frontiers in Nutrition, 2023)
Background and aims Multiple sclerosis (MS) is associated with osteoporosis, possibly due to neurological disability and decreased calcium intake. The objective of this study was to evaluate the efficacy of a personalized nutritional advice program by a dietitian compared to the delivery of a standard advice form to optimize dietary calcium intake in outpatients with MS. Methods We performed a randomized, controlled, parallel trial comparing the efficacy of a personalized dietary advice (PDA) program to standard advice form (SAF) to increase daily calcium intake in MS patients. The study population was composed by patients with relapsing-remitting MS aged 18–69 years old. PDA program consisted in dietary advice delivered by a dietitian at baseline, 1 month, and 3 months. Calcium and nutrient intake in patients from both groups was evaluated at baseline and 6 months using a dietary survey. Results Of the 194 patients screened for inclusion, 182 patients were included (79% female, median age of 42 years, and median EDSS of 2.0), and randomized to SAF (n = 92) or PDA (n = 90). At 6 months, median calcium intake increased by 241 mg/day in the PDA group and decreased by 120 mg/day in the SAF group (p < 0.0001). However, the median calcium intake was 947 mg/day in the SAF group and 778 mg/day in the PDA group at baseline (p = 0.0077), potentially favoring the effect of dietary advice. Complementary analyses focusing on patients with insufficient calcium intakes at baseline revealed comparable values in both groups (p = 0.69). Of those, patients included in the PDA group obtained significantly higher calcium intakes at 6 months than patients from the SAF group (p = 0.0086) independently of EDSS, PASAT, HADS and EQ-5D scores. Conclusion This work shows the efficacy of dietary management based on personalized advice program over 3 months to durably increase calcium consumption in MS patients with insufficient calcium intake. Clinical trial registration clinicaltrials.gov, identifier NCT02664623.